Negative List in Services Liberalization for ASEAN Developing Countries - Setiawan, Sigit (International Journal of Economics and Financial Issues, 2018)
Recently, several new FTAs/RTAs involving ASEAN developing countries have emerged with different services negotiation modalities, one of them is to adopt or migrate to negative list for scheduled commitments. The change surely brings concerns among ASEAN developing countries. This study is intended to first, analyse the pros and cons for ASEAN developing countries in migrating to negative list; secondly, to analyze various potential issues that ASEAN countries may encounter in migrating to negative list and how to address such issues. To reach the objectives, descriptive analysis method is adopted, relevant literature and FTA agreements are analyzed, and two series of Focus Group Discussions were held. Several potential issues are identified and probable solutions are provided in this study, with regard to protection for new services and new financial services, the transposition of GATS style positive list to negative list, template headnotes, consistency, safeguard, and foreign control. Keywords: FTAs/RTAs, services liberalization, negative list, ASEAN JEL Classifications: F13, H87, K33, O24